4-Hydroxy-2-nonenal induces endothelial cell injury via PKCdelta and biphasic JNK activation - Goya, Sho; Hirata, Haruhiko; Hoshino, Shigenori; Inoue, Koji; Kashiwa, Yozo; Kawase, Ichiro; Kijima, Takashi; Kumagai, Toru; Mayumi, Masahiko; Osaki, Tadashi; Suzuki, Mayumi; Tachibana, Isao; et al. (Technische Universität Dortmund, 2008)
4-Hydroxy-2-nonenal (4-HNE), a major product generated during oxidative stress, exhibits cytotoxic effects; however, the mechanisms of 4-HNE-induced endothelial cell injury are not well defined. To explore this issue, we examined how 4-HNE damages human umbilical vein endothelial cells (HUVECs) and found that 4-HNE induced biphasic activation of c-Jun N-terminal kinase (JNK). Both pre- and post-treatment of HUVECs with SP600125, a specific JNK inhibitor, significantly suppressed the cytotoxic effects of 4-HNE. Inhibition of protein kinase Cd (PKCd), which was also phosphorylated by 4-HNE, reduced endothelial cell injury as well as late-phase JNK phosphorylation elicited by 4-HNE. Inversely, pre-treatment of HUVECs with SP600125 suppressed PKCd activation. Taken together, these results support the concept that 4-HNE induces vascular endothelial cell injury by the interaction between biphasic JNK activation and the PKCd pathway.
EXCLI Journal ; Vol. 7, 2008
Keywords: 4-Hydroxy-2-nonenal; Cd; cell injury; c-Jun N-terminal kinase; endothelial cell; kinase; oxidative stress; protein; 610